La lingua eccentrica. Le parole tra estesiologia e morfologia della cultura - Russo, Marco (Rivista Italiana di Filosofia del Linguaggio, 2013)
Plessner’s  reflection on language becomes interesting only from the point of view of his theory of man as an excentric animal. In this paper I’ll present a specific part of this theory, namely the “esthesiology of mind”, a study of the main cultural forms in their systematic connection with perception, performances and symbolic languages. A very similar approach is Cassirer’s morphology of culture, to which I refer too in order to point out the innovation of Plessner’s esthesiology. It lies in the central role of our living body and  his differentiated sensibility,  which is essential to understand the different types of making sense. According to Cassirer and Plessner only by studying systematically cultural forms we can analyze human cognition; furthermore Plessner emphasizes the role of the specific embodiments of mind and symbols. That is why I give account of language’s intermediate position between abstraction and empathy, between the formal signs of hard science and the expressive signs of humanities. A position which also mirrors the ambiguous nature of human being.